Strain-mediated spin-orbit torque enhancement in Pt/Co on flexible substrate - Wong, Grayson Dao Hwee (2022)
Current-induced magnetization switching by spin-orbit torque generated in heavy metals offers an enticing realm for energy-efficient memory and logic devices. The spin Hall efficiency is a key parameter in describing the generation of spin current. Recent findings have reported enhancement of spin Hall efficiency by mechanical strain, but its origin remains elusive. Here, we demonstrate a 45% increase in spin Hall efficiency in the platinum/cobalt (Pt/Co) bilayer, of which 78% of the enhancement was preserved even after the strain was removed. Spin transparency and X-ray magnetic circular dichroism revealed that the enhancement was attributed to a bulk effect in the Pt layer. This was further confirmed by the linear relationship between the spin Hall efficiency and resistivity, which indicates an increase in skew-scattering. These findings shed light on the origin of enhancement and are promising in shaping future utilization of mechanical strain for energy-efficient devices.